The Impact of The Prestige of Institution Type on Professional Satisfaction - Vályogos, Krisztina (Central European Journal of Educational Research, 2024)
Teachers are doing their job despite notoriously low pay, and the extrinsic and intrinsic factors that keep them in the profession are the subject of national and international research. In the present study, we investigate the subjective sense of professional success of teachers in secondary vocational education in the light of the type of institution in which they teach. Their questionnaire survey was carried out online (N=166) during the pandemic period, having been adapted to the situation. We wanted to assess factors of their sense of professional success, which are partly related to the classical role of a teacher, such as knowledge transfer, education of or cooperation with other actors in education, but also to hypothetical factors such as self-training and creativity. Our hypothesis that the prestige of the institution type and the professional satisfaction of the teacher are related was not confirmed, but the identified factors played a different role to varying degrees.